A novel technique proposed for automatic control of small hydro power plants. (25th May 2005) - Goyal, Himani; Bhatti, T.S.; Kothari, D.P.
A new scheme is proposed for the speed control of hydro turbines. Power can be controlled by controlling the rotary motion of the spear valve or linear motion of the sluice gate. In this paper, necessity for speed control, various function of governors, types, speed regulation of micro-hydroelectric power plants, functional block diagram of power generation and control system general models for speed-governing systems for hydro systems, conventional governors used, various block diagram of a hydro turbine speed control system are discussed along with derivation of hydraulic turbine transfer function. A new model is proposed model for controlling the flow by controlling the rotary motion of the spear valve or linear motion of the sluice gate by using servomotor and using the principle of servomechanisms. Then, general function of the servomotor and different types of feedback control systems are also discussed. An analogy of the conventional system is given with the proposed system using the principle of Type 0 servomechanism. This scheme will provide complete control of the generation and thereby maintain the frequency of the system at the desired level.